Penerapan Akad Musyarakah Mutanaqisyah Sebagai Alternatif Solusi Pembiayaan KPR Dalam Perbankan Syariah - Fatimah, Emi Sri Rahayu; Sapa, Nasrullah bin; Wijaya, Abdi (IQRO: Journal of Islamic Education, 2023)
This article discusses the application of musyarakah mutanaqisyah related to KPR (Home Ownership Credit) financing in the sharia banking system. The purpose of this article is to provide an overview of the application of the musyarakah mutanaqisyah contract as an alternative KPR (Home Ownership Credit) financing solution in sharia banking. Apart from that, this article also analyzes the obstacles in implementing musyarakah mutanaqishah contracts on KPR (Home Ownership Credit) in sharia banking. The research method used is the library research method or library study. Literature studies are devoted to revealing information sourced from scientific texts originating from books or scientific journals that are relevant to the topic being discussed. The research results obtained show that the application of the musyarakah mutanaqishah contract in mortgage financing in sharia banking has several advantages as an alternative solution in sharia financing, namely where the bank and the customer both own an asset that is the object of the agreement. Because they have mutual rights to do so, banks and customers mutually maintain the agreed cooperation.